Comprehensive Physiology 2012
DOI: 10.1002/cphy.c110007
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics of Exercising Humans

Abstract: Human muscles, limbs and supporting ventilatory, cardiovascular, and metabolic systems are well adapted for walking, and there is reasonable transfer of efficiency of movement to bicycling. Our efficiency and economy of movement of bipedal walking (≈30%) are far superior to those of apes. This overall body efficiency during walking and bicycling represents the multiplicative interaction of a phosphorylative coupling efficiency of ≈60%, and a mechanical coupling efficiency of ≈50%. These coupling efficiencies c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 120 publications
1
30
0
Order By: Relevance
“…The results showed that the average W EXT from a standing position was very close to theoretical work (0.4% difference). We also found, in agreement with the literature [7,32,33], an expected value for mechanical work efficiency of 25-30%.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that the average W EXT from a standing position was very close to theoretical work (0.4% difference). We also found, in agreement with the literature [7,32,33], an expected value for mechanical work efficiency of 25-30%.…”
Section: Discussionsupporting
confidence: 92%
“…Hypotheses generated over the last two decades from comparative physiologists (Hochachka et al, 1999) and anthropologists (Bramble and Lieberman, 2004) suggest that the combined traits of superior endurance capacity and an impressive ability to thermoregulate permitted ancestral humans from the high plains of East Africa to succeed as game hunters and thereby obtain high-protein sources of food that were essential for the emergence of larger brains and complex cooperative behavior. Human skeletal muscles, limbs, and the supporting ventilatory, cardiovascular, and metabolic systems were well suited for upright locomotion, with economy of movement for bipedal walking and running far exceeding that of other primates (Bramble and Lieberman, 2004;Brooks, 2012). At this time, lifestyle and energy availability were inextricably linked to the periodic cycles of feasts and famines, with certain genes evolving to regulate efficient storage and utilization of endogenous fuel stores, the so-called ''thrifty genes'' (Neel, 1962).…”
Section: Why Study Exercise?mentioning
confidence: 99%
“…A myriad of intrinsic biochemical factors influence the relative contributions of fat and carbohydrate to energy expenditure during exercise (Spriet & Watt, ; Brooks, ), but extrinsic factors such as the intensity and mode of exercise are important regulators of substrate utilization (Romijn et al., ; van Loon et al., ; Achten et al., ; Knechtle et al., ). The contribution of fat to energy expenditure is greatest during low‐ and moderate‐intensity exercise but declines thereafter (Romijn et al., ; van Loon et al., ).…”
mentioning
confidence: 99%